2019
DOI: 10.21873/anticanres.13674
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Head and Neck Cancer Patients Who Undergo Resection, But Forgo Adjuvant Therapy

Abstract: Background/Aim: This study aimed to evaluate the outcomes of patients with head and neck squamous cell carcinoma (HNSCC) who underwent resection and refused the recommended adjuvant therapy. Patients and Methods: Locoregional recurrence-free survival (LRRFS) and time to progression (TTP) were assessed in HNSCC patients treated with surgery who declined some or all adjuvant therapy (refusal group (RG)) compared to those who received the recommended adjuvant therapy (TG). Results: With a median follow-up of 23 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…The foundational trials underlying PORT recommendations did not definitively establish a survival benefit. 34,35 Although retrospective institutional data have also shown mixed results, 30,36 one large population-based study detected a nearly 10% survival improvement with PORT in all head and neck cancer types. 8 National Comprehensive Cancer Network (NCCN) guidelines currently recommend PORT for patients with HPV-associated OPSCC with advanced pathologic stage or high-risk pathological features.…”
Section: Discussionmentioning
confidence: 99%
“…The foundational trials underlying PORT recommendations did not definitively establish a survival benefit. 34,35 Although retrospective institutional data have also shown mixed results, 30,36 one large population-based study detected a nearly 10% survival improvement with PORT in all head and neck cancer types. 8 National Comprehensive Cancer Network (NCCN) guidelines currently recommend PORT for patients with HPV-associated OPSCC with advanced pathologic stage or high-risk pathological features.…”
Section: Discussionmentioning
confidence: 99%
“…A further potential reason for refusing AT might be the fear of potential adverse effects, which has been reported in various investigations. 15 We suggest that the data from this study might help to guide decision-making in evaluating the advantages and disadvantages of AT. Previous studies reported low socioeconomic status, increased age, distance to treatment facility, and female sex as risk factors for refusal.…”
Section: Discussionmentioning
confidence: 88%
“…In this observational matched cohort study, we present data on 82 patients who either received or refused the recommended AT after primary resection of advanced OSCC. Although AT has been established in the treatment of oral cancer for over 30 years, there are only a few studies reporting outcome measures in patients withdrawing from AT . While these studies focused on human papillomavirus–associated OPSCC and HNSCC in general, there was until now, to our knowledge, no study reporting data from OSCC in particular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since outcome of patients with locally advanced SCCHN require improvement, many preclinical and clinical studies have been conducted during recent years (17)(18)(19)(20)(21)(22). The prognoses of patients with SCCHN are particularly poor, if unresectable or incompletely resected.…”
Section: Discussionmentioning
confidence: 99%